Pengaruh Geometri Jalan terhadap Produktivitas Batubara di Pit 2 Banko - Shoffan Shofa Hamdan Nurullah; Dono Guntoro; Indra Karna Wijaksana (UPT Publikasi Ilmiah Unisba, 2024)
Abstract. PT XYZ is a coal mining company that employs four mining stages in its operations: ripping, digging, loading, and hauling. The digging-loading equipment used is the Volvo 480D, and the hauling equipment is the Volvo FMX400. The hauling process significantly impacts the achievement of production targets. In January, the coal production from Pit 2 fleet 1 reached 93% of the production target. Several road geometry conditions can affect the speed of the hauling equipment, impacting the production targets. To address the issue of slowing hauling equipment, data such as the actual speed of the hauling equipment from each road segment, the weight of the hauling equipment, road geometry, and classification of resistance values are needed to determine the actual rimpull value. Reducing the rimpull value involves evaluating and improving the mining roads, considering factors such as road grade, cross slope, superelevation, and the surface material of the mining roads that affect the rolling resistance. Road grade changes were implemented in segments C-D and J-L. After evaluating and improving the roads, theoretically, the loaded travel time decreased to 3.1 minutes, and the empty travel time decreased to 1.8 minutes. Consequently, coal production increased from 91,826 BCM/month to 127,100 BCM/month, a production increase of 28.8%. Abstrak. PT XYZ adalah perusahaan pertambangan batubara yang dalam proses penambangannya meliputi empat tahapan: ripping, digging, loading, dan hauling. Alat gali-muat yang digunakan adalah Volvo 480D, sementara alat angkutnya adalah Volvo FMX400. Proses pengangkutan sangat mempengaruhi pencapaian target produksi. Pada bulan Januari, produksi batubara di Pit 2 fleet 1 mencapai 93% dari target produksi. Beberapa kondisi geometri jalan mempengaruhi kecepatan alat angkut saat hauling, yang berdampak pada pencapaian target produksi. Untuk mengatasi perlambatan laju alat angkut, diperlukan data seperti kecepatan alat angkut aktual dari setiap segmen jalan, berat alat angkut, geometri jalan, dan klasifikasi nilai ketahanan untuk mengetahui besaran nilai rimpull aktual. Pengurangan nilai rimpull dilakukan dengan mengevaluasi dan memperbaiki jalan tambang, baik dari geometri jalan seperti grade, cross slope, dan superelevasi, maupun dari material permukaan jalan tambang yang mempengaruhi nilai rolling resistance. Perubahan grade jalan dilakukan pada segmen C-D dan J-L. Setelah evaluasi dan perbaikan jalan, secara teoritis, waktu berangkat bermuatan menjadi 3,1 menit, sedangkan waktu berangkat kosong menjadi 1,8 menit. Produksi batubara pun meningkat dari 91.826 BCM/bulan menjadi 127.100 BCM/bulan, atau terjadi kenaikan produksi sebesar 28,8%.